A decision tree for acute oral toxicity: Implementing the last resort requirement in practice - Giorgia Pallocca; Patricia Bishop; Patience Browne; Marie Darracq-Ghitalla-Ciock; Fabian A. Grimm; Laura Holden; Jay Ingram; Kamel Mansouri; Hans Raabe; Clive S. Roper; Katherine Santizo; Barbara G. Schmitt; et al. (Regulatory Toxicology and Pharmacology, 2026)

Beyond NAMs versus animal models: Context of use as the governing framework for integrated nonclinical strategies in drug development - Stefano Gaburro; Brian Berridge; Nicholas W. Kelley; Eckhard von Keutz; Marc Ferrer; Clive Roper; Michael J. Fossler; Jeffrey J. Bajramovic; Jean-Pierre Valentin; Timothy McGovern; Todd Bourcier; Ronald L. Wange; et al. (Regulatory Toxicology and Pharmacology, 2026)

ESTIV early career network: A growing initiative to support the next generation of NAMs-oriented toxicologists - Mohamed F. Abdallah; Luiz Ladeira; Peter Pôbiš; Andreas O. Stucki; Bambou Xuezhu Tan; Benoit Maisonneuve; Clive Roper; Helena Kanďárová (Toxicology in Vitro, 2026)

The Decision Tree approach as a strategy for the global phase out of animal testing for acute and local toxicity for chemicals: recommendations from an expert workshop - Catherine Willett; Giorgia Pallocca; Annamaria Carusi; Nathalie Alépée; Patience Browne; Marie Darracq-Ghitalla-Ciock; Fabian A. Grimm; Jay Ingram; Laura Holden; Kamel Mansouri; Hans Raabe; Clive Roper; et al. (Regulatory Toxicology and Pharmacology, 2026)

Minimum information for reporting on the TEER (trans-epithelial/endothelial electrical resistance) assay (MIRTA) - Monita Sharma; Erin Huber; Emma Arnesdotter; Holger P. Behrsing; Adam Bettmann; David Brandwein; Samuel Constant; Rahul Date; Abhay Deshpande; Eric Fabian; Amit Gupta; Robert Gutierrez; et al. (Archives of Toxicology, 2025)
Standard information reporting helps to ensure that assay conditions and data are consistently reported and to facilitate inter-laboratory comparisons. Here, we present recommendations on minimum information for reporting on the TEER (trans-epithelial/endothelial electrical resistance) assay (MIRTA). The TEER assay is extensively used to evaluate the health of an epithelial/endothelial cell culture model and as an indicator of the potential toxicity of a test substance. This publication is the result of an international collaboration─called the RespTox (Respiratory Toxicity) Collaborative─through which twelve laboratories shared their protocols for assessing the barrier function of respiratory epithelial cells using the TEER assay following exposure to substances. The protocols from each laboratory were reviewed to identify general steps for performing the TEER assay, interlaboratory differences between steps, the rationale for differences, whether these differences impact results or cross-laboratory comparisons between TEER measurements. While the MIRTA recommendations are focused on respiratory epithelial cell systems, these recommendations can be adapted for other cell systems that form barriers. The use of these recommendations will support data transparency and reproducibility, reduce challenges in data interpretation, enable cross-laboratory comparisons, help assess study quality, and facilitate the incorporation of the TEER assay into national and international testing guidance.

A comparative study of the in vitro dermal absorption of radiolabeled benzophenone through human skin - Sadaff Ejaz; Clive Roper; Zoe Finlayson; Kyle S. Saitta; Timothy McCarthy; Frank Sun; Michael D. Southall (Toxicology in Vitro, 2024)

ESTIV 2022: Key enabling non-animal technologies for research, education and testing - Helena Kandárová; Clive Roper; Marketa Dvořáková (Toxicology in Vitro, 2024)

Skin barrier function for regulatory skin absorption tests and effects on testosterone and sucrose absorption - Thomas Brackin; Heather Gayes; Ian Johnson; David Fox; Clive Roper (Toxicology in Vitro, 2024)

Assessment of the utility of the novel Phenion® full thickness human skin model for detecting the skin irritation potential of antimicrobial cleaning products - Kathryn Page; Walter Westerink; Kristie Sullivan; Thomas McDonald; Clive Roper (Toxicology in Vitro, 2024)

Prediction of the percutaneous penetration and metabolism of dodecyl decaethoxylate in rats using in vitro models - Clive S. Roper; Doug Howes; Peter G. Blain; Faith M. Williams (Archives of Toxicology, 1995)